User-Driven Toponym Disambiguation Using Dialogue - Muroň, Mikuláš; Dařena, František; Procházka, David; Kern, Roman (Routledge Journals, Taylor & Francis Ltd., 2024)
The paper presents a novel method for processing information with a spatial component or querying geospatial databases. It proposes an interactive toponym disambiguation method tailored especially for dialogue systems and chatbots. The method exploits the interactive nature of dialogues to resolve ambiguity by using dialogue clarification techniques, i.e., asking users for additional information to perform disambiguation. The paper evaluates different questioning strategies and methods for selecting suitable toponym features to formulate disambiguation questions. A novel Equi-population partitioning method for selecting suitable toponym features in questions is presented as an approach outperforming other compared methods.
Keywords: toponym disambiguation; dialog systems; dialog clarification